Analysis of the Role of Work Environment to Increase Employees Performance on the Changes in Status of BUMN to PT. PNM - Lenni Lukitasari; Tita Ayu Alliffia (Almana : Jurnal Manajemen dan Bisnis, 2022)
Since November 2, 2021, PT. Permodalan Nasional Madani (Persero) officially relinquished its company status to PT. Permodalan Nasional Madani became a subsidiary of PT Bank Rakyat Indonesia Tbk which is a Holding Ultra Micro (UMi) entity. This change was carried out in the hope of increasing and expanding the empowerment provided by PNM to micro-enterprises so that they can develop into a bigger ones. This study aims to describe the role of the employee's environment in improving employee performance at PT. National Capital Madani Sukajadi Branch and the impact after the change in company status. This study uses descriptive methods with qualitative descriptive analysis techniques with eight people as sources. The result describes that the work environment has a positive influence on the performance of employees of PT. National Capital Madani Sukajadi Branch. The change in the ownership status of the company has not yet had a significant impact because it is still premature. The company can maintain a good work environment by focusing more on the comfort of the work situation, providing support for adequate facilities, and increasing the suitability of rewards. These efforts can increase employee morale and will have an impact on increasing the company's overall performance.